Analisis Respons Hidrologi untuk Mendukung Perencanaan Pengelolaan Sub-DAS Opak Hulu, Daerah Istimewa Yogyakarta - Nicko Widiatmoko; Suria Darma Tarigan; Enni Dwi Wahjunie (Institut Pertanian Bogor, 2020)
Land use change is one of the causes of the decreasing of hydrological function that affects the hydrological response of a watershed. Planning of watershed management needs to be conducted to improve the hydrological function of the watershed. This study aims to determine the hydrological response in supporting watershed management planning in Opak Hulu Watershed. This research was conducted using the Soil and Water Assessment Tool (SWAT) hydrological modeling. The method used included data collection, processing of input data, running of SWAT model, calibration, validation, and the decision of the best watershed management scenarios. The results of the analysis of land use changes in the Opak Hulu Watershed in 2012–2017 had a significant increase in mixed upland agriculture (3.21%) and shrubs (1.43%). Meanwhile, open field (2,31%) and dry land agriculture (1.71%) decreased significantly. Based on the analyzed hydrological scenario, Soil and Water Conservation techniques can decrease the surface runoff and increase the lateral flow and base flow. The scenario is able to decrease the surface runoff by 542.22 mm (27.09%). It increases lateral flow and base flow by 321.82 mm (13.15%) and 797.28 mm (18.32%), respectively. The best watershed management planning with Soil and Water Conservation technique is able to reach Annual Flow Coefficient value to 0,33 (moderate) and 69,85 (moderate) for Flow Regime Coefficient. Keywords: land use, soil and water conservation techniques, SWAT model, watershed